2017
DOI: 10.1038/s41598-017-11556-8
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of cigarette smoking and occupational noise exposure on hearing loss: evidence from the Dongfeng-Tongji Cohort Study

Abstract: Combined effect of cigarette smoking and occupational noise exposure on hearing loss has rarely been evaluated among Chinese population, especially among females. This cross-sectional study was conducted in 11196 participants of Dongfeng-Tongji cohort study. Smoking status was self-reported through questionnaire and occupational noise exposure was evaluated through workplace noise level and/or the job titles. Hearing loss was defined as a pure-tone mean of 25 dB or higher at 0.5, 1, 2, and 4 kHz in both ears. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 35 publications
5
26
0
Order By: Relevance
“…Four studies not published in Chinese or English were also excluded. Our meta-analysis includes 27 studies [7,[10][11][12][13]19,20,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] in this meta-analysis. Selection details are shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies not published in Chinese or English were also excluded. Our meta-analysis includes 27 studies [7,[10][11][12][13]19,20,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] in this meta-analysis. Selection details are shown in Figure 1.…”
Section: Literature Searchmentioning
confidence: 99%
“…may be independent factors or have a synergistic effect with noise to increase the risk of NIHL. Smoking is a risk factor for many illnesses, and many published studies [10][11][12][13] have suggested that it may also be associated with NIHL. Some toxic and harmful substances like nicotine from tobacco burning may affect hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cigarette smoking has been implicated in the increased susceptibility to noise damage https://www.ncbi.nlm.nih.gov/pmc/articles/PMC5593900/- CR19. The combination of smoking and occupational noise exposure can synergistically affect hearing, especially in elderly male participants 16 . In addition, individuals with the longest acoustic exposure duration and maximum pack-years are more at risk.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking is an intrinsic risk factor for hearing loss. Moreover, it may synergistically influence hearing when associated with occupational noise exposure, particularly in males and older subjects 16 . Noise over-stimulation induces inflammatory responses and the up-regulation of pro-inflammatory cytokines in the inner ear 3 …”
Section: Introductionmentioning
confidence: 99%
“…The sample size of these studies was relatively small, and they failed to take other risk factors into consideration. For example, aging [19], and the use of alcohol and tobacco [20] and other harmful chemicals [21] will aggravate the progress of NIHL, while female sex is a protective factor [22]. Another study explored the classi cation of noise-susceptible and noise-resistant workers based on the ISO 1999:1990 standard [23]; however, the results depended on the statistical distribution of hearing threshold levels of a speci c noise-exposed population, and have become arbitrary.…”
Section: Introductionmentioning
confidence: 99%